2013
DOI: 10.1007/s11356-013-1744-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perchlorate on growth of four wetland plants and its accumulation in plant tissues

Abstract: Perchlorate contamination in water is of concern because of uncertainties about toxicity and health effects, impact on ecosystems, and possible indirect exposure pathways to humans. Therefore, it is very important to investigate the ecotoxicology of perchlorate and to screen plant species for phytoremediation. Effects of perchlorate (20, 200, and 500 mg/L) on the growth of four wetland plants (Eichhornia crassipes, Acorus calamus L., Thalia dealbata, and Canna indica) as well as its accumulation in different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…The results were in agreement with earlier findings that Cd stress decreased chlorophyll contents for both rice cultivars with Cd-sensitive genotype being more severely affected [21]. In our previous study, it was also observed that when treated with 500 mg/L perchlorate, chlorophyll content of four wetland plants showed significant decline contrasted to control groups [30].…”
Section: Physiological Responsessupporting
confidence: 93%
“…The results were in agreement with earlier findings that Cd stress decreased chlorophyll contents for both rice cultivars with Cd-sensitive genotype being more severely affected [21]. In our previous study, it was also observed that when treated with 500 mg/L perchlorate, chlorophyll content of four wetland plants showed significant decline contrasted to control groups [30].…”
Section: Physiological Responsessupporting
confidence: 93%
“…Suyunuo, IR65598-112-2, and khazar showed the greatest decrease, and gannuoxiang was less affected. A number of studies also have documented significant differences in ClO 4 bioaccumulation ability among species [19,21,23] or genotypes within the same species [24,25]. In our previous study [21], significant differences were also observed in growth inhibition among 4 wetland plants by ClO 4 -.…”
Section: Perchlorate Phytotoxicity To Different Rice Varietiesmentioning
confidence: 54%
“…We found, however, that the decrease varied with rice varieties. In our previous study [21], significant differences were also observed in growth inhibition among 4 wetland plants by ClO 4 -. Previous studies have found a wide variability in the sensitivity of rice genotypes to different environmental stresses, which is exploited in the selection of plant types resistant to such harsh conditions [26,30,33,34].…”
Section: Perchlorate Phytotoxicity To Different Rice Varietiesmentioning
confidence: 65%
See 1 more Smart Citation
“…Perchlorate was observed in high concentration in soybean sprouts (Glycine max L. Merr), water dropwort (Oenanthe stolonifera DC), and lotus root (Nelumbo nucifera Gaertn [Yang and Her, 2011]). The wetland plants like Eichhornia crassipes, Acorus calamus L., Thalia dealbata and Canna indica show perchlorate accumulation (He et al, 2013). Edible cole crops (Brassica sp.)…”
Section: Fate and Transportmentioning
confidence: 99%